Sustainable Concrete Production: Utilizing Cow Dung Ash and Corn Stalk Ash as Eco-Friendly Alternatives - Jamwal, Aakash; Nautiyal, Akhilesh; Singh, Kanwarpreet; Alam, Shamshad; Alselami, Nimer Ali; Aati, Khaled M. (Civil Engineering Journal, 2024)
This study aims to determine whether it is feasible to replace conventional materials used in manufacturing concrete with waste materials, namely cow dung ash and corn stalk ash. This study proposes to assess the possibility of using these agricultural by-products to improve the sustainability of concrete while simultaneously tackling the environmental issues related to the manufacture of conventional concrete. The research aims to assess the mechanical qualities, optimize the mix proportions, and examine the ecological implications of using these substitute materials. This research aims to mitigate environmental challenges like carbon dioxide emissions, resource depletion, and the accumulation of agricultural waste by combining agricultural waste and lowering dependency on traditional cement. The study investigates the use of cow dung ash (CDA) and corn stalk ash (CSA) as alternatives for conventional Portland cement (OPC) in mortar mixes at varying quantities, ranging from 5% to 25% CDA and 2.5% to 10% CSA. Chemical composition reveals that CDA and CSA predominantly comprise O, Mg, Al, Si, P, K, and Ca. The workability, hardened characteristics, and microstructure of CDA and CSA were assessed. Increasing CDA and CSA percentages reduced mortar workability; nevertheless, replacing 8% to 10% CDA and 7.5% CSA maintained compressive, tensile, and flexural strengths comparable to control mixes. However, more significant CDA and CSA proportions resulted in lower mortar strength. For example, 10% CDA-enriched mortar had a compressive strength of 31.77 N/mm2, a tensile strength of 3.42 N/mm2, and a flexural strength of 3.61 N/mm2, whereas 7.5% CSA-enriched mortar had a compressive strength of 28.4 N/mm2, a tensile strength of 3.04 N/mm2, and a flexural strength of 3.7 N/mm2. According to the findings, CDA and CSA can replace OPC by up to 10% and 7.5% in mortar manufacturing, making cementitious material alternatives viable. Doi: 10.28991/CEJ-SP2024-010-02 Full Text: PDF